2(-8x-2y=-22)
16x+7y=17
-16x-4y=-44
16x+7y=17
3y=-27
y=-9
16x+7(-9)=17
16x+-63=17
16x=80
X=5
Answer: Use the PEMDAS rule
Step-by-step explanation: 0z+3z+5=2(z-3)=
z= -1
you need to do the z numbers all together and the normal numbers together then subtract them to get -1
I hope that I help you
Answer:
x = 54°
y = 66°
Step-by-step explanation:
x + y = 120° (given)
x = y - 12
Then, y + y - 12 = 120°
(y + y) - 12 = 120°
2y - 12 = 120°
2y = 120 + 12 = 132°
y = 132/2 = 66°
x = y - 12 = 66 - 12 = 54°
There you go :)
Answer:
A = 43°
b = 25.8 (3 sig. fig.)
c = 14.5 (3 sig. fig.)
Step-by-step explanation:
Using angle sum of triangle, we get A = 180 - 104 - 33 = 43°
Using sin law,
b/sin104 = 18.1/sin43
b = 25.8 (3 sig. fig.)
c/sin33 = 18.1/sin43
c = 14.5 (3 sig. fig.)
Answer:
The numbers increase by 3
Step-by-step explanation:
The difference between all the numbers in the sequence have a gap of 3
9 and 12 --gap of 3
12 and 15--gap of 3
18 and 21--gap of 3
21 and 24--gap of 3